Co-Design of a Public Space and the Implementation: Atakent (Car) Park - Koray Velibeyoğlu; Pelin Özden (Journal of Architectural Sciences and Applications, 2023)
Citizen Design Science is a new co-design strategy for urban and architectural systems that improves the planning, design, management, and renewal of cities, urban habitats, and architectural structures, using active design tools through citizens' observation, experience, and local knowledge. The aim of this study is to describe how Atakent Parking Area is transformed into a public space design and implementation through both digital and analog active design tools in the co-design process that includes citizens' spatial experiences, needs, and desires through the method of citizen design science. The objective indicators and subjective perception applied in the study were combined in the co-design process to implement an urban design project. The experimental collaborative urban design process is realized on a democratic platform based on the tendencies and expectations of the participants. Two conceptual urban design projects were prepared with design science data including citizens' wishes, needs, and suggestions about the area, and participating citizens were asked to vote for the project democratically in the urban space. The selected conceptual design project was transformed into an implementation project in the urban area.